BUMDES STRATEGY IN THE DEVELOPMENT OF WONG PULUNGAN HOT SPRINGS TRANSIT TOURISM - Azizah, Aprilia Nur; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the strategy of Gempol Village-Owned Enterprises (BUMDes) in developing the transit tourism potential of Wong Pulungan Hot Springs as one of the village's economic and social assets. The focus of the research is directed at four main indicators, namely strategy planning, implementation, evaluation and supervision, and sustainability aspects, in order to understand the extent to which BUMDes governance is able to optimize the potential of local-based tourism independently. Method: Using a qualitative descriptive approach method, with data collection techniques through in-depth interviews with BUMDes managers, community leaders, and visitors, complemented by field observation and documentation. The analysis was carried out by examining the empirical narrative based on strategic themes developed according to the research indicators. Results: The results of the study show that BUMDes Gempol has been working on participatory planning of the community and village apparatus, the implementation of gradual development, informal evaluation and supervision, and community involvement in maintaining cleanliness and the ecosystem. However, BUMDes Gempol still faces several shortcomings such as the absence of a long-term strategic plan document, limitations in digital promotion, informal evaluations, and collective awareness that needs to be improved. Novelty: The novelty of this study lies in the strategic mapping based on village institutional performance indicators in the context of transit tourism management, which is still rarely the focus of academic studies. This study shows how BUMDes institutions can play a role as actors of local development through a collaborative approach, although limited by limited resources and minimal formal policy support.